The Influence and Analysis of Multimedia Interaction on the Development of Dance - Haijian Wu; Yan Leng (Journal of Electrical and Computer Engineering)
Since ancient times, dance has been widely loved by people. The history of dance has a long history, and people’s pursuit of dance has never stopped. However, with the development of modern technology, traditional dance has been unable to keep up with the pace of the times. Therefore, this article studies the influence of multimedia interaction on the development of dance. This article proposes that multimedia interaction has a great influence on the status quo of dance development. This article aims to study the role of multimedia interaction in dance development. In the eleven years since 2010, the technology of stage effects has developed rapidly. As you can imagine, not only the stage effects can bring a visual feast, but also the development space of dancers has been greatly improved. It can be seen that multimedia interaction is of great significance to the development of dance; with the rapid development of science and technology, multimedia technologies such as computer networks are widely used in all walks of life. The application in the field of dance art is gradually popularized, in which dance teaching and stage performance methods have undergone great changes with the in-depth popularization of multimedia. Therefore, this article must analyze the influence of multimedia interaction on the development of dance.